The Muppets take Manhattan - Oz, Frank; Henson, Jim; Goelz, Dave; Whitmire, Steve, 1959-; Moss, Jeffrey (Culver City, Calif. : Sony Pictures Home Entertainment, 2012)
After a successful college run, the Muppets decide to take their musical "Manhattan Melodies" to Broadway.
Originally released as a motion picture in 1984.
Features: bonus trailers, interactive menus, muppetisms: Miss Piggy and Kermit the Frog, Pepe and Fozzie Bear, interview with Jim Henson, scene selection.
Cinematography, Robert Paynter ; production design, Paul Eads, Stephen Hendrickson ; art direction, Paul Eads, W. Steven Graham ; film editor, Evan A. Lottman ; music, Jeff Moss.
Jim Henson, Frank Oz, Dave Goelz, Steve Whitmire, Richard Hunt.
MPAA rating: G.
DVD, Dolby digital mono.
Keywords: Muppets -- Drama; Musical films; Puppet films; Fiction films; Video recordings for the hearing impaired; Feature films; Comedy films